First draft genome sequence data report of Listeria innocua SA_AR with Listeria pathogenicity island 3 virulence genes isolated from raw chicken in BangladeshNCBInor - Supantha Rivu; Md. Abu Raihan; Sangita Ahmed (Data in Brief, 2025)
The draft genome sequence of Listeria innocua SA_AR obtained from raw chicken of Kaptan Bazar, Dhaka (23° 43′ 20'' north, 90° 24′ 47'' east) is reported here. L. innocua is an important species of the Listeria genus that usually infects birds and ruminants, and rarely humans. Qiagen DNeasy Blood & Tissue Kit was used for genomic DNA extraction from a single colony. Sequencing was performed via Illumina MiSeq. The assembly produced 18 contigs, with an N50 value of 1,567,498 and an L50 of 1. The genome size was 2,802,079 bp, and the average GC content was 37.41 %. Prokka v.1.14.6 was utilized for genome annotation and gene predictions, which identified 2786 coding sequences, 3 rRNA genes and 43 tRNA genes. Five antibiotic resistance genes (mdrL, lin, norB, fosX, and mprF), 2 copper resistance genes (copC, and csoR), 4 CRISPRS and one CAS-cluster (TypeIB) were identified in the strain. Notably, 17 virulence genes were detected, among which 4 genes (llsA, llsG, llsH, and llsX) belonged to the Listeria pathogenicity island 3, indicating to its virulence potential. Genome sequence of Listeria innocua SA_AR has been deposited at the National Center for Biotechnology Information (NCBI) under accession number JBJXVH000000000.